KERALA Elections and After - K HARIDAS (Economic and Political Weekly May 27, 2006, 2006)
Whatever be the truth regarding the theory of the successive erosion of the United Democratic Front's mass base, it would be presumptuous to attribute to the poll outcome much more than what is denoted by the popular phrase of anti-incumbency. This of course, notwithstanding the V S Achutanandan factor. Now with the new state ministry in office, given the factional divide in the state CPI(M), if things are decided on the basis of mere pragmatic considerations or compromises worked out to satiate warring factions, the high hopes of the people might sooner than later give way to frustration.